Association between maternal comorbidity and preterm birth by severity and clinical subtype: retrospective cohort study - Le Thi; Auger Nathalie; Park Alison L; Luo Zhong-Cheng (BMC, 2011)
Abstract Background Preterm birth (PTB) is a major cause of infant morbidity and mortality, but the relationship between comorbidity and PTB by clinical subtype and severity of gestational age remains poorly understood. We evaluated associations between maternal comorbidities and PTB by clinical subtype and gestational age. Methods We conducted a retrospective cohort study of 1,329,737 singleton births delivered in hospitals in the province of Québec, Canada, 1989-2006. PTB was classified by clinical subtype (medically indicated, preterm premature rupture of membranes (PPROM), spontaneous preterm labour) and gestational age (< 28, 28-31, 32-36 completed weeks). Odds ratios (OR) of PTB by clinical subtype for systemic and localized maternal comorbidities were estimated using polytomous logistic regression, adjusting for maternal age, grand multiparity, and period. Attributable fractions were calculated. Results PTB rates were higher among mothers with comorbidity (10.9%) compared to those without comorbidity (4.7%). Several comorbidities were associated with greater odds of medically indicated PTB compared with no comorbidity, but only comorbidities localized to the reproductive system were associated with spontaneous PTB. Drug dependence and mental disorders were strongly associated with PPROM and spontaneous PTBs across all gestational ages (OR > 2.0). At the population level, several major comorbidities (placental abruption, chorioamnionitis, oliogohydramnios, structural abnormality, cervical incompetence) were key contributors to all clinical subtypes of PTB, especially at < 32 weeks. Major systemic comorbidities (preeclampsia, anemia) were key contributors to PPROM and medically indicated PTBs. Conclusions The relationship between comorbidity and clinical subtypes of PTB depends on gestational age. Prevention of PPROM and spontaneous PTB may benefit from greater attention to preeclampsia, anemia and comorbidities localized to the reproductive system.